Women ward commissioner of reserved seat in urban local government (Municipality) of Bangladehsh: problem and prospect - Hossain, Md. Mahbub (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2008.